A construção de significado da legalidade no controle jurisdicional de políticas públicas na área de saúde: uma análise retórica. - Porto, Simone Peixoto Ferreira (2023)
This thesis argues that the Brazilian Supreme Court (Supremo Tribunal Federal – STF), when deciding on public health policies, presents itself as analytical or descriptive, that is, as more interested in the empirical knowledge of reality, an essential stance to confer the mark of scientificity on legal discourses and the environment of logos, of analytical logic. However, in practice, its performance is predominantly marked by the persuasive dimension of rhetoric related to emotions and ideological constructions, an environment of pathos, but also of ethos, without this characterizing an affront to the legitimacy of the jurisdictional control of public policies. The Federal Constitution of 1988 gave to the Brazilian Supreme Court the role of ultimate interpreter of normative discourse, a context in which we propose to unveil how rhetorical strategies are used to legitimize normative constructions shaped under the influence of the persuasive rhetorical route related to emotions (pathos). Such analyses will be carried out in addition to our theoretical investigations into the issues underlying the principle of legality and the fundamental right to health seen as a discourse. This is because we understand that legality, an axiom of the Rule of Law, and the right to health, a corollary of “equality” and the requirement of a State committed to social well-being, are linguistic expressions that enshrine ideologically antagonistic positions. Judicialization as a reflection of a linguistic phenomenon of normative construction, the crisis of the traditional principle of administrative legality and legal consequentialism as a hermeneutic proposal will also be the subject of our investigations. Addressing these issues will provide support so that, at the end of this work, with the help of Aristotelian rhetorical evidence and stylistics, we can understand the processing of human language in the realization of the right to health through jurisdiction and, consequently, how the construction of the meaning of legality is done in the jurisdictional control of public health policies. The research selects some rhetorical methodology strategies: epoché (refraining from taking any side at first); dissoi logoi (“divergent arguments”: confronting antagonistic positions and not only exposing ideas with which one agrees). It is, therefore, an empirical qualitative research, based on bibliographic and documentary sources. We will also use the case study method, through which, based on a rhetorical perspective of law, we intend to deconstruct a decision of the Supreme Court whose purpose is to comply with public policies in the area of health. Therefore, based on the textual elements extracted from the decision handed down in the Extraordinary Appeal with General Repercussion nº 657.718/MG, we will provide a realistic description of the construction of the meaning of legality by the highest body of the Brazilian Judiciary, the Supreme Court.